Peningkatan Kemampuan Komunikasi Mahasiswa Melalui Metode Student Team Achievement Division (STAD) Berbasis Lesson Study For Learning Community (LSLC) - Didik Iswahyudi; Mochammad Ramli Akbar (Jurnal Inspirasi Pendidikan, 2018)
This research was conducted to improve the communication ability of Pancasila and Citizenship Education (PPKn) Students through Student Team Achievement Division (STAD) method based on Lesson Study for Learning Community (LSLC) with discussion and debate on the subject of Democracy Theory for 6 (six) meetings or Classroom Action Research cycle, using lesson plan and chapter design that was developed together with the curriculum development team of PPKn study program. Based on the research conducted, the conclusions can be drawn are: (1) Lesson study able to give positive effect to the students and lecturers on the learning process that increase from meeting to meeting. (2) Discussion and debate activities in Lesson Study activities from cycle I to VI have significant improvement, ranging from passive discussion to heated debate on the basis of consideration that began empirical on the subject of Democratic Theory. (3) Group or group of students has increased, ranging from passive discussion and dominated by one group, to debate with equal ability in all groups. (4) A more representative class of nomenclature and volume so that discussion and debate are more effective and efficient for good learning process.